Analisis Urf terhadap Sistem Jaminan dalam Praktik Mappasanra Cengkeh di Kabupaten Bulukumba - Hasan, Nugraha; Nursyam, Fatima (Universitas Islam Negeri Alauddin Makassar, 2024)
This study aims to find out how the guarantee system in the practice of clove tree mappasanra, especially in the community of Tamaona Village, Kindang District, Bulukumba Regency. The type of research conducted is field research which is raised from the observation of social facts studied by the method of sociological approach and sharia juridical approach. The sources of data for this research are people who practice pawnning, community leaders, and religious leaders. The data collection method is carried out by means of observation, interviews, and documentation. The results of this study show that the people of Tamaona Village, Kindang District, Bulukumba Regency still carry out the practice of clove tree mappasanra because they consider that this practice is one of the quick and easy ways to get a cash loan with a system of pawning the clove tree as collateral to be managed and all the proceeds are taken by the pawnbroker until the pawnbroker pays off the debt. There are 2 forms of collateral utilization by murtahin, namely the use of collateral by murtahin with a time limit and the utilization of collateral by murtahin without a time limit. In the view of Islamic law based on 'urf, it is viewed that the guarantee system in the practice of mappasanra carried out by the community is categorized into 'urf fasid because it tends to harm one of the parties, namely the pawnbroker and is included in the agreement that leads to the category of usury. The implication of this study is that the practice of clove tree mappasanra is expected to continue to be carried out guided by the rules of Islamic law, to religious leaders or the government to convey about muamalah especially pawns in accordance with Islamic law so that the community is able to apply the system in the practice of mappasanra in accordance with applicable rules.